Plasmodium vivax: Polymorphism in the Merozoite Surface Protein 1 Gene from Wild Colombian Isolates (2000)
Gutierrez, A., Vicini, J., Patarroyo, M. E., Murillo, L. A., and Patarroyo, M. A. 2000. Plasmodium vivax: Polymorphism in the merozoite surface protein 1 gene from wild colombian isolates. Experimental Parasitology95, 215–219. The Plasmodium vivax merozoite surface protein-1 (PvMSP-1) has been considered a candidate for a malaria vaccine against erythrocytic stages. PvMSP-1 is immunogenic during natural infections and exhibits antigenic polymorphism. The extent of genetic polymorphism in a region between the so-called interspecies conserved blocks (ICBs) 2 and 4 of the PvMSP-1 was analyzed in 20 isolates taken from patients from two different areas in Colombia. Variation is unevenly distributed along this gene segment among the isolates. Comparative analysis of these sequences led to the definition of five sequence types (ST1 to 5). ST1 to ST4 exhibit a variation pattern associated with sequences present in the Salvador or Belem sequences. However, ST5 has clusters of sequence that have not been previously described. The changes found along the five variants confirm the important role of recombinational and/or gene conversion events in generating allelic diversity.